Knowledge on Stage: Public Roles of Scientists In Times of Communicative Abundance - Fabrino, Ricardo; Castelfranchi, Yurij (Javnost-The Public, 2022)
This article explores the challenges and dilemmas the current scenario of communicative abundance poses to experts and scientists that are willing to influence policy-making (or that are dragged to arenas of political debates). It identifies eight contemporary challenges worth noting: (1) dissemination of disinformation; (2) scepticism towards science and experts; (3) multiplication of voices with public resonance; (4) volume and (in)accessibility of data; (5) polarisation and fragmentation of publics; (6) algorithmic distribution of communication; (7) grammars of current public communication; and (8) a complex interplay between visible and invisible discursive arenas. It, then, discusses the strategies used by scientists to deal with these challenges in the context of the Covid-19 Pandemic. It does so through a series of illustrations drawn from visible scientists acting in the Brazilian public sphere. Despite the fact that novel strategies and innovative adaptions are noticed, the article also points to the resilience of top-down forms of communication.